Penatalaksanaan kehilangan gigi posterior dengan implan dental - Dwiseptyoga, Senyan; Suwandi, Trijani (Jurnal Kedokteran Gigi Terpadu, 2022)
Background : Dental implant is one of the options to restore extracted tooth with fixed partial denture. This method of restoration is popular because of the ability of dental implant to replace the teeth without disturbing neighboring hard and soft tissues with very high long term survival rate. Dental implant procedure should be planned and executed with proper procedure to get an esthetic and functional restoration. This case report will discuss the treatment planning and procedure of placing of single unit implant placement on posterior tooth Case report : A 26-year-old woman came with complain of extracted lower right tooth 2 years ago and she wanted a fixed prosthesis to replace this tooth. Straumann BLT dental implant of diameter 4.1x Height 10mm is placed on this patient after treatment planning with radiograph image and study model analysis. Screw-cemented retained prosthesis was delivered on the implant to restore the function and esthetic of the missing 47 tooth. Conclusion : Planning and proper procedure during implant placement and restoration will lead to a good long-term esthetic and functional outcome.